Respuesta :
Answer:
y = 3x-1
Step-by-step explanation:
So basically you have to translate this into slope intercept form which is y=mx+b. You plug in m and b thats how you get it.
y = 3x - 5
Basically, all you do is plug in the values into the equation y=mx+b.
x=1
y=-2
m=3
-2 = 3(1) +b
-2 = 3 + b
-5 = b
So, the equation is y = 3x - 5. You can check by plugging just the x value.
y = 3(1) - 5
y = 3 - 5
y = -2
Basically, all you do is plug in the values into the equation y=mx+b.
x=1
y=-2
m=3
-2 = 3(1) +b
-2 = 3 + b
-5 = b
So, the equation is y = 3x - 5. You can check by plugging just the x value.
y = 3(1) - 5
y = 3 - 5
y = -2